CONTEXTUAL CHEMISTRY LEARNING MODEL BASED ON ENVIRONMENT TO IMPROVE LEARNING OUTCOMES AND ACADEMIC HONESTY OF JUNIOR HIGH SCHOOL - ., Sugiarti (Journal of Educational Science and Technology, 2015)
This study aims at determining the steps the development, validity, practicality and effectiveness of the model PKKBL through the measurement of learning outcomes and academic honesty junior high school students. PKKBL models equipped learning tools that help teachers and students make the learning process so that the learning outcomes of chemical and academic honesty students can be better than before. This research is the development of a model refers to the Borg and Gall (1983) that modofied into seven steps. Subject of research is the students of SMPN 30 Makassar VII6 class. Data collection tool uses observation sheets, questionnaires, worksheets, and achievement test sheet which has been validated. Data analysis techniques performed by descriptive qualitative and quantitative descriptive percentages. The result showed that: (1) PKKBL models can be developed through three stages of development, namely stages: (a) the initial study, (b) a limited test phase, and (c) the testing phase is extended, (2) the model PKKBL which has been developed showing: (a) instruments are valid models (4.3) and reliable (0.85), (b) the device is practically used (1.6) and (c) because the effectiveness may improve learning outcomes (82,28) and the students academic honesty belonging to adequate category (72.0). Keywords: Teaching Chemical Model, Contextual, Environment, Learning   Outcomes,      Academic Honesty